30.3k views
5 votes
Simplifying each side of the equation results in x2 − 3x − 4 = x2 − 5x + 6.

Find the solution:
x + 2
3x

1
x − 2
=
x − 3
3x

x =

User TheAlse
by
5.1k points

2 Answers

6 votes

Answer:

x = 5

Explanation:

hope this helps!

User Vadim Ashikhman
by
5.4k points
4 votes

Answer:

x = 5

Explanation:

x² -3x -4 = x² - 5x + 6.

-x² - x²

-3x -4 = -5x + 6

+3x + 3x

-4 = -2x +6

-6 -6

-10 = -2x

÷-2 ÷-2

5 = x

Hope this Helps

User Massives
by
6.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.